2022
DOI: 10.1177/1934578x221142797
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Immunomodulatory Effect of TCM Formulas Containing Either Astragali Radix or With This Replaced by Hedysari Radix

Abstract: Hedysari Radix (Hong Qi) is a commonly substituted material with similar functions to Astragali Radix (Huang Qi). However, it is still misused as Huang Qi, even though people know they are different species. This study aims to find evidence that Hong Qi can replace Huang Qi in traditional Chinese medicine (TCM) formulas used for immunomodulation. Therefore, we evaluated the immunomodulatory effects of both medicines on dendritic cells. The water extract of Hong Qi showed a more substantial immunomodulatory eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It has the properties of tonifying qi and ascending yang, strengthening the exterior and reducing sweat, nourishing blood for promoting the production of fluid, pus‐draining, and toxin expulsion, and promoting wound healing in sore muscles. Hedysari Radix is rich in pharmacologically active constituents such as flavonoids, polysaccharides, saponins, and amino acids, which possess immunomodulatory, antioxidant, antitumor, hypoglycemia, and anti‐aging properties [1–3]. Studies have shown that Hedysari Radix antagonizes the immunosuppressive effects of cyclophosphamide and other drugs [4].…”
Section: Introductionmentioning
confidence: 99%
“…It has the properties of tonifying qi and ascending yang, strengthening the exterior and reducing sweat, nourishing blood for promoting the production of fluid, pus‐draining, and toxin expulsion, and promoting wound healing in sore muscles. Hedysari Radix is rich in pharmacologically active constituents such as flavonoids, polysaccharides, saponins, and amino acids, which possess immunomodulatory, antioxidant, antitumor, hypoglycemia, and anti‐aging properties [1–3]. Studies have shown that Hedysari Radix antagonizes the immunosuppressive effects of cyclophosphamide and other drugs [4].…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, CDs can also be easily prepared using a large number of low-cost and readily available green precursors as raw materials, showing the obvious advantages of being natural, non-toxic, and renewable [23,24]. Radix Hedysari, a time-honored folk herb used in traditional China, has good pharmacological effects [25,26] attributed to the various components of flavonoids, triterpenoids and triterpenoid saponins, coumarins, organic acids, and polysaccharides [27,28]. In addition to their efficacy in diseases, these ingredients have also shown good biological activity, which would act as an excellent carbon source.…”
Section: Introductionmentioning
confidence: 99%